The Renew® anal insert for passive faecal incontinence: a retrospective audit of our use of a novel device. (12th March 2019) - Leo, C. A.; Thomas, G. P.; Hodgkinson, J. D.; Segal, J. P.; Maeda, Y.; Murphy, J.; Vaizey, C. J.
Abstract: Aim: The Renew® anal insert is a recent treatment for patients who suffer from passive faecal incontinence (FI). Our aim was to assess the effectiveness of the insert and patients' satisfaction with it. Method: A retrospective audit of patients who were treated with the Renew® anal insert was undertaken. The St Mark's Incontinence Score was used to evaluate clinical outcome. Renew® size, the number of inserts used per day and per week had also been recorded. Subjective assessment of symptoms, how beneficial Renew® was and how satisfied patients were with the device were all recorded. Major events and side effects were also noted. Results: Thirty patients received Renew® as a treatment for passive incontinence in 2016. The median St Mark's Incontinence Score was 15 (range 7–18) at baseline and 10 (range 2–18) at first follow‐up ( P < 0.0001) at a median of 11 (range 8–14) weeks. Eleven (37%) patients used the regular size and 19 (63%) the large size. Patients used an average of 1.67 inserts per day (range 1–3) on an average of 3.58 days per week (1–7). Three patients reported a deterioration in symptoms, seven (23%) had no change and 20 (67%) showed a significant improvement. Six patients (20%) did not like the device while 24 (80%) liked it. Seventeen patients (57%) wanted to continue this treatment in the long term. Conclusion: The Renew® device seems to be an acceptable and effective therapeutic option for passive FI. Further work is needed to compare it with other treatments and establish its position in the treatment pathway.